A new sunflower high oleic mutation confers stable oil grain fatty acid composition across environments - Alberio, Constanza (2016)
The oil industry demands sunflower oils with high oleic acid content. New varieties producing high oleicoils independently of the growing environment are needed as growers could receive an extra prime foroffering them. Oil fatty acid composition of high oleic sunflower hybrids currently available carrying thePervenets mutation could however be affected by the temperature during the grain filling period. A newhigh oleic mutation has been obtained to attain oils with ultra-high oleic levels (>90%oleic acid content).This new structural mutation would be able to reduce the variation in oleic acid percentage to changes inthe minimum night temperature (MNT). The aim of this work was to assess the response of oil fatty acidcomposition of the new high oleic mutation to MNT compared to traditional and Pervenets genotypes.Field experiments in different sowing dates and locations and one growth chambers experiment wereperformed to explore a wide range of temperatures (11.8–23.2◦C) during grain filling. The oleic acid per-centage in traditional and high oleic Pervenets genotypes varied between 15.0–50.9% and 87.4–91.2%,respectively, while the new mutation genotype presented values of oleic acid between 91.3 and 92.5%.Moreover, the oleic acid percentage of traditional and Pervenets genotypes showed a linear and positiveresponse to temperature (slopes 2.95 and 0.28%oleic acid◦C−1, respectively). No response to tempera-ture was detected in the new mutation genotype. The ultra-high oleic quality from the new high oleicsunflower mutant could be obtained in a wide range of environments as the fatty acid composition wasnot affected by temperature during grain filling, representing an advantage over the high oleic Pervenetsand traditional genotypes.